Reinforced anti-cracking concrete for assembled buildings and preparation method thereof

By using polyacrylamide particles and montmorillonite to prepare crack-resistant and curing agents in concrete, the encapsulation properties and interface structure of cement paste were improved, solving the problem of easy cracking of concrete in prefabricated buildings and achieving an improvement in strength and crack resistance.

CN117209226BActive Publication Date: 2025-01-07TONGLU BENTENG BUILDING MATERIALS PROD CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311179138.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-01-07
Estimated Expiration
2043-09-13

AI Technical Summary

Technical Problem

Concrete in prefabricated buildings is prone to cracking, and existing technologies are insufficient to effectively improve its strength and crack resistance.

Method used

A crack-resistant agent and a curing agent were prepared by mixing polyacrylamide particles with montmorillonite. By improving the encapsulation properties of cement paste and the interfacial structure of concrete, an interpenetrating network structure was formed, which reduced stress concentration, reduced crack formation, and promoted the hydration process.

Benefits of technology

It significantly improves the compressive strength and crack resistance of concrete, and reduces the drying shrinkage rate and total crack area.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention discloses a reinforced anti-cracking concrete for prefabricated buildings and a preparation method thereof, including the following process: take fly ash, river sand, coarse aggregate and one-half of the water of the component and mix them, stir for 5 to 8 minutes, add cement, anti-cracking agent and water reducer in sequence and mix them fully, continue stirring for 5 to 10 minutes, add water of the remaining components, stir evenly, and obtain slurry; pour, spray curing agent 60 minutes and 150 minutes after pouring, and perform curing to obtain concrete. The present invention obtains a monomer copolymerized with acrylamide and acrylic acid by reacting phenylboric acid with diallylpentylamine to obtain polyacrylamide, which is added to concrete materials, and can thicken the cement slurry formed by cement and water, cooperate with the water reducer to reduce the water bleeding rate, improve the encapsulation of cement slurry to the mixing materials river sand, fly ash, coarse aggregate, etc., and improve the strength of the prepared concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-cracking concrete, in particular to a reinforced anti-cracking concrete for assembled buildings and a preparation method thereof. Background Art

[0002] Concrete is an engineering composite material in which cementitious materials bind aggregates into a whole. It is a basic building material and the most widely used and largest basic material in the world today. The production of concrete for prefabricated buildings is a key link in the development of prefabricated buildings. With the development of modern civil engineering, higher requirements are placed on its strength and crack resistance. As a quasi-brittle material, concrete has poor toughness and is prone to cracking and other problems. Plastic shrinkage is prone to occur in the early stage of concrete pouring, which produces internal stress and causes cracking hazards. Therefore, we propose a reinforced anti-cracking concrete for prefabricated buildings and a preparation method thereof. Summary of the invention

[0003] The object of the present invention is to provide a reinforced anti-cracking concrete for prefabricated buildings and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing reinforced anti-cracking concrete for prefabricated buildings, comprising the following processes:

[0005] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 5 to 8 minutes, add cement, anti-cracking agent and water reducing agent in turn and mix thoroughly, continue stirring for 5 to 10 minutes, add the remaining water, stir evenly to obtain slurry; pour, spray curing agent 60 minutes and 150 minutes after pouring, and cure to obtain concrete.

[0006] Furthermore, the slurry includes the following components by mass: 320 parts of cement, 55 parts of fly ash, 745 parts of river sand, 1072 parts of coarse aggregate, 157 parts of water, 3.8-6.0 parts of water reducing agent, and 20.6-30.5 parts of anti-cracking agent.

[0007] Further, the cement is 42.5 grade Portland cement with a fineness of 0.8%;

[0008] The fineness of fly ash is 13%, the water requirement ratio is 100%, and the loss on ignition is 2.1%;

[0009] The fineness modulus of river sand is 2.9 and the apparent density is 2630kg / m3;

[0010] The coarse aggregate includes 214 parts of small stones with a continuous grade of 5 to 20 mm in size and 858 parts of large stones with a continuous grade of 20 to 40 mm in size;

[0011] The water reducer is a polycarboxylate water reducer, which was purchased from Suzhou Xingbang Chemical Building Materials Co., Ltd.

[0012] Furthermore, the anti-cracking agent is prepared by the following process:

[0013] S1. Take dichloromethane, add phenylboric acid and diallylpentylamine, mix, introduce oxygen, add organic boron, pyridine and cuprous oxide, react at 80-85°C and 4.0MPa for 24h to obtain a monomer;

[0014] S2. Take deionized water, add monomer and acrylamide to mix to obtain an acrylamide solution;

[0015] Adding acrylic acid aqueous solution and ammonium persulfate aqueous solution, reacting at 50-60° C. for 40-60 minutes to obtain polyacrylamide aqueous solution; drying and crushing to obtain polyacrylamide particles;

[0016] The polyacrylamide aqueous solution is prepared into a 0.5-2.0% finishing solution, the polypropylene fiber is immersed in the solution, and the solution is soaked at a temperature of 45-55°C for 24 hours, and then the treated fiber is taken out and air-dried to obtain the treated fiber;

[0017] Mixed with polyacrylamide particles, an anti-cracking agent is obtained.

[0018] Furthermore, the molar ratio of the phenylboric acid, diallylamine, organic boron, pyridine and cuprous oxide is 1:(1.0-1.1):(0.08-0.11):(0.20-0.22):3.

[0019] Diallylpentylamine, CAS number is 959026-14-3.

[0020] Furthermore, the ratio of diallylamine to dichloromethane is (0.80-0.85) mol / L, and oxygen is introduced to 0.4 MPa.

[0021] The organic boron was a boron trifluoride ether solution with a mass concentration of 30%, which was purchased from Shanghai Titan Technology Co., Ltd.

[0022] Furthermore, the mass ratio of deionized water, monomer, and acrylamide in the acrylamide solution is (20-50):(0.3-0.5):1.

[0023] Furthermore, the volume ratio of the acrylamide solution, the acrylic acid aqueous solution, and the ammonium persulfate aqueous solution is 100:50:0.5.

[0024] Furthermore, the mass concentration of the acrylic acid aqueous solution is 25-30%, and the mass concentration of the ammonium persulfate aqueous solution is 10%.

[0025] Furthermore, the mass ratio of the polypropylene fiber to the finishing liquid is 1:(10-20).

[0026] Furthermore, the mass ratio of polyacrylamide particles to treated fibers in the anti-cracking agent is 1:(1-3).

[0027] Furthermore, the polypropylene fiber has a length of 28 mm, a diameter of 0.8 mm, a density of 0.95 g / cm3, a tensile strength of 540 MPa, and an elastic modulus of 7.1 GPa.

[0028] In the above technical scheme, phenylboric acid reacts with the amino group in diallylpentylamine to obtain aromatic amino acid ester, which is recorded as a monomer; it forms a redox system with ammonium persulfate, and the secondary carbon ortho-nitrogen in the monomer initiates the active point, which can generate carbon free radicals and oxygen free radicals. The initiating active point on the secondary carbon further initiates free radical polymerization to form a branched chain, and the chain end free radicals terminate through coupling to form a cross-linked structure, thereby obtaining a polyacrylamide with a branched structure, which has a high molecular weight and improved apparent viscosity and stability; when added to concrete materials, it can thicken the cement slurry formed by cement and water, cooperate with the water reducer to reduce the water bleeding rate, improve the encapsulation of the cement slurry on the mixing materials such as river sand, fly ash, coarse aggregate, etc., and improve the strength of the produced concrete. The polypropylene fiber is treated in a polyacrylamide aqueous solution, and a layer of polyacrylamide film is attached to the surface of the polypropylene fiber. When added to concrete materials, the hydrophilic groups form hydrogen bonds with the hydration products, thereby improving the interface structure between the polypropylene fiber and the concrete, and improving the bonding performance between the polypropylene fiber and the concrete. The polyacrylamide on the treated fiber surface and in the polyacrylamide particles is hydrolyzed after being blended with the concrete materials, and the original carboxyl groups in the polyacrylamide molecular structure cooperate with calcium ions, aluminum ions, etc. in the concrete slurry to promote the hydration process, generate a viscous gel, and interact with the hydration products to form a rigid interpenetrating network structure, strengthen the interaction between the hydration products, reduce stress concentration, fill the pores, reduce the generation of cracks at the interface, improve the density of the prepared concrete, and can improve the flexural and compressive strengths of the concrete, and improve its earthquake resistance and crack resistance.

[0029] Furthermore, the curing agent is prepared by the following process:

[0030] Take polyacrylamide particles and water, mix them, add sodium hydroxide, heat to 95°C and hydrolyze for 2 hours; add montmorillonite and surfactant, mix them, and obtain a curing agent.

[0031] Furthermore, the ratio of polyacrylamide particles to water is (15-35) g / L.

[0032] Furthermore, the mass ratio of polyacrylamide particles to montmorillonite is 1:(3.7-4.2); and the sodium hydroxide is 2.0-2.5% of the mass of polyacrylamide.

[0033] Furthermore, the surfactant is hexadecyltrimethylammonium bromide, which accounts for 0.8-0.9% of the mass of the polyacrylamide particles.

[0034] Furthermore, the montmorillonite is sodium montmorillonite, has a particle size of 200 mesh, a density of 1.8 g / cm3, and a pH value of 8.0.

[0035] In the above technical scheme, the prepared hydrolysis product of polyacrylamide is mixed with montmorillonite and surfactant to prepare a curing agent, which is sprayed on the concrete surface to form a stable and dense surface film, which can effectively inhibit the evaporation of water on the concrete surface, increase the internal humidity of the concrete, and promote the hydration of the gel material; and keep a certain amount of moisture on the concrete surface to avoid dehydration and cracking of the concrete, reduce the early shrinkage of the concrete, and improve the crack resistance of the concrete. The hydrolysis of polyacrylamide reduces its viscosity, makes its molecular conformation more extended, and enhances the interaction with the cationic surfactant hexadecyltrimethylammonium bromide, which promotes the film formation of polyacrylamide on the concrete surface; and the presence of sodium carboxyl in the polyacrylamide hydrolysis product enhances its binding ability with montmorillonite and makes the dispersion of montmorillonite more uniform; and montmorillonite, as a layered silicate, enables the polyacrylamide hydrolysis product to be intercalated in the interlayer structure of montmorillonite, and when water molecules enter the interlayer structure, it exists in the curing agent in the form of sol, and forms a three-dimensional network structure with the polyacrylamide hydrolysis product, which is conducive to the film formation of the curing agent on the concrete surface and the enhancement of the concrete surface.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] The reinforced anti-cracking concrete for prefabricated buildings of the present invention and the preparation method thereof are as follows: phenylboric acid is reacted with diallylpentylamine to obtain a monomer which is copolymerized with acrylamide and acrylic acid to obtain polyacrylamide, which is added to concrete materials to thicken cement slurry formed by cement and water, cooperate with a water reducer to reduce water bleeding rate, improve the encapsulation of cement slurry on mixing materials such as river sand, fly ash, coarse aggregate, etc., and improve the strength of the prepared concrete. DETAILED DESCRIPTION

[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0039] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 5 minutes, add cement, anti-cracking agent and water reducer in turn and mix them thoroughly, continue stirring for 5 minutes, add the remaining water, stir evenly to obtain slurry;

[0040] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 3.8kg / m 3 Water reducing agent, 20.6kg / m 3 Anti-cracking agent;

[0041] pouring, spraying curing agent 60min and 150min after pouring, curing, and obtaining concrete;

[0042] The anti-cracking agent is made by the following process:

[0043] S1. Take dichloromethane, add phenylboric acid and diallylpentylamine, mix, introduce oxygen, add organic boron, pyridine and cuprous oxide, react at 80°C and 4.0MPa for 24h to obtain a monomer;

[0044] S2. Take deionized water, add monomer and acrylamide to mix, and obtain acrylamide solution; add acrylic acid aqueous solution and ammonium persulfate aqueous solution, react at 50°C for 40 minutes, and obtain polyacrylamide aqueous solution; dry and crush to obtain polyacrylamide particles; prepare the polyacrylamide aqueous solution into a 0.5% finishing liquid, immerse the polypropylene fiber, soak at 45°C for 24 hours, take out and dry, and obtain treated fiber; mix with polyacrylamide particles to obtain an anti-cracking agent;

[0045] The molar ratio of phenylboric acid, diallylamine, organic boron, pyridine and cuprous oxide is 1:1:0.08:0.20:3; the ratio of diallylamine and dichloromethane is 0.80 mol / L, and the oxygen is introduced to 0.4 MPa; the mass ratio of deionized water, monomer and acrylamide in the acrylamide solution is 20:0.3:1; the mass concentration of the acrylic acid aqueous solution is 25%, and the mass ratio of the polypropylene fiber and the finishing liquid is 1:10; the mass ratio of the polyacrylamide particles and the treated fiber in the anti-cracking agent is 1:1;

[0046] The curing agent is prepared by the following process:

[0047] Take polyacrylamide particles and water, mix them, add sodium hydroxide, heat to 95°C and hydrolyze for 2 hours; add montmorillonite and surfactant, mix them, and obtain a curing agent;

[0048] The ratio of polyacrylamide particles to water is 15 g / L; the mass ratio of polyacrylamide particles to montmorillonite is 1:3.7; the sodium hydroxide is 2.0% of the mass of polyacrylamide; the surfactant is hexadecyltrimethylammonium bromide, which is 0.8% of the mass of polyacrylamide particles. Example 2

[0049] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 6 minutes, add cement, anti-cracking agent and water reducer in turn and mix them thoroughly, continue stirring for 8 minutes, add the remaining water, stir evenly to obtain slurry;

[0050] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 5.0kg / m 3 Water reducing agent, 25.6kg / m 3 Anti-cracking agent;

[0051] pouring, spraying curing agent 60min and 150min after pouring, curing, and obtaining concrete;

[0052] The anti-cracking agent is made by the following process:

[0053] S1. Take dichloromethane, add phenylboric acid and diallylpentylamine, mix, introduce oxygen, add organic boron, pyridine and cuprous oxide, react at 82°C and 4.0MPa for 24h to obtain a monomer;

[0054] S2. Take deionized water, add monomer and acrylamide to mix, and obtain acrylamide solution; add acrylic acid aqueous solution and ammonium persulfate aqueous solution, react at 55°C for 50 minutes, and obtain polyacrylamide aqueous solution; dry and crush to obtain polyacrylamide particles; prepare the polyacrylamide aqueous solution into a 1.2% finishing liquid, immerse the polypropylene fiber, soak at 50°C for 24 hours, take out and dry, and obtain treated fiber; mix with polyacrylamide particles to obtain an anti-cracking agent.

[0055] The molar ratio of phenylboric acid, diallylamine, organic boron, pyridine and cuprous oxide is 1:1.05:0.10:0.21:3; the ratio of diallylamine and dichloromethane is 0.82 mol / L, and the oxygen is introduced to 0.4 MPa; the mass ratio of deionized water, monomer and acrylamide in the acrylamide solution is 35:0.4:1; the mass concentration of the acrylic acid aqueous solution is 27%, and the mass ratio of the polypropylene fiber and the finishing liquid is 1:15; the mass ratio of the polyacrylamide particles and the treated fiber in the anti-cracking agent is 1:2.

[0056] The curing agent is prepared by the following process:

[0057] Take polyacrylamide particles and water, mix them, add sodium hydroxide, heat to 95°C and hydrolyze for 2 hours; add montmorillonite and surfactant, mix them, and obtain a curing agent;

[0058] The ratio of polyacrylamide particles to water is 25 g / L; the mass ratio of polyacrylamide particles to montmorillonite is 1:4.0; the sodium hydroxide is 2.2% of the mass of polyacrylamide; and the surfactant is hexadecyltrimethylammonium bromide, which is 0.85% of the mass of polyacrylamide particles. Example 3

[0059] Take fly ash, river sand, coarse aggregate and half of the water, mix them and stir for 8 minutes, then add cement, anti-cracking agent and water reducing agent in turn and mix them thoroughly, continue stirring for 10 minutes, add the remaining water and stir evenly to obtain slurry;

[0060] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 6.0kg / m 3 Water reducing agent, 30.5kg / m 3 Anti-cracking agent;

[0061] pouring, spraying curing agent 60min and 150min after pouring, curing, and obtaining concrete;

[0062] The anti-cracking agent is made by the following process:

[0063] S1. Take dichloromethane, add phenylboric acid and diallylpentylamine, mix, introduce oxygen, add organic boron, pyridine and cuprous oxide, react at 85°C and 4.0MPa for 24h to obtain a monomer;

[0064] S2. Take deionized water, add monomer and acrylamide to mix, and obtain acrylamide solution; add acrylic acid aqueous solution and ammonium persulfate aqueous solution, react at 60°C for 60 minutes to obtain polyacrylamide aqueous solution; dry and crush to obtain polyacrylamide particles; prepare the polyacrylamide aqueous solution into a 2.0% finishing liquid, immerse the polypropylene fiber, soak at 55°C for 24 hours, take out and dry, and obtain treated fiber; mix with polyacrylamide particles to obtain an anti-cracking agent.

[0065] The molar ratio of phenylboric acid, diallylamine, organic boron, pyridine and cuprous oxide is 1:1.1:0.11:0.22:3; the ratio of diallylamine and dichloromethane is 0.85 mol / L, and the oxygen is introduced to 0.4 MPa; the mass ratio of deionized water, monomer and acrylamide in the acrylamide solution is 50:0.5:1; the mass concentration of the acrylic acid aqueous solution is 30%, and the mass ratio of the polypropylene fiber and the finishing liquid is 1:20; the mass ratio of the polyacrylamide particles and the treated fiber in the anti-cracking agent is 1:3.

[0066] The curing agent is prepared by the following process:

[0067] Take polyacrylamide particles and water, mix them, add sodium hydroxide, heat to 95°C and hydrolyze for 2 hours; add montmorillonite and surfactant, mix them, and obtain a curing agent;

[0068] The ratio of polyacrylamide particles to water is 35 g / L; the mass ratio of polyacrylamide particles to montmorillonite is 1:4.2; the sodium hydroxide is 2.5% of the mass of polyacrylamide; and the surfactant is hexadecyltrimethylammonium bromide, which is 0.9% of the mass of polyacrylamide particles. Comparative Example 1

[0069] The anti-cracking agent is made by the following process:

[0070] Deionized water is taken, and dimethylaminoethyl methacrylate and acrylamide are added to mix to obtain an acrylamide solution; an acrylic acid aqueous solution and an ammonium persulfate aqueous solution are added, and the mixture is reacted at 50°C for 40 minutes to obtain a polyacrylamide aqueous solution; the mixture is dried and crushed to obtain polyacrylamide particles; the polyacrylamide aqueous solution is configured into a 0.5% finishing liquid, and polypropylene fibers are immersed in the liquid at a temperature of 45°C for 24 hours, and the fibers are taken out and dried to obtain treated fibers; the treated fibers are mixed with the polyacrylamide particles to obtain an anti-cracking agent;

[0071] The mass ratio of deionized water, dimethylaminoethyl methacrylate and acrylamide in the acrylamide solution is 20:0.3:1; the mass concentration of the acrylic acid aqueous solution is 25%, the mass ratio of the polypropylene fiber and the finishing liquid is 1:10; the mass ratio of the polyacrylamide particles and the treated fiber in the anti-cracking agent is 1:1;

[0072] The other processes are the same as those in Example 1. Comparative Example 2

[0073] The anti-cracking agent is made by the following process:

[0074] Take deionized water, add acrylic acid and acrylamide, mix, and then add ammonium persulfate aqueous solution, react at 50°C for 40 minutes to obtain a polyacrylamide aqueous solution; dry and crush to obtain polyacrylamide particles; prepare the polyacrylamide aqueous solution into a 0.5% finishing liquid, immerse the polypropylene fiber, soak at 45°C for 24 hours, take out and dry to obtain treated fiber; mix with polyacrylamide particles to obtain an anti-cracking agent;

[0075] The mass ratio of deionized water, acrylic acid and acrylamide is 20:0.5:1; the mass ratio of polypropylene fiber and finishing liquid is 1:10; the mass ratio of polyacrylamide particles in the anti-cracking agent and treated fiber is 1:1;

[0076] The other processes are the same as those in Example 1. Comparative Example 3

[0077] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 8 minutes, add cement and water reducer in turn and mix them thoroughly, continue stirring for 10 minutes, add the remaining water, stir evenly to obtain slurry;

[0078] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 6.0kg / m 3 Water reducing agent;

[0079] pouring, spraying curing agent 60min and 150min after pouring, curing, and obtaining concrete;

[0080] The preparation process of the curing agent is the same as that of Example 1. Comparative Example 4

[0081] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 8 minutes, add cement and water reducer in turn and mix them thoroughly, continue stirring for 10 minutes, add the remaining water, stir evenly to obtain slurry;

[0082] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 6.0kg / m 3 Water reducing agent;

[0083] pouring, spraying curing agent 60min and 150min after pouring, curing, and obtaining concrete;

[0084] The preparation process of the curing agent is the same as that of Comparative Example 1. Comparative Example 5

[0085] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 8 minutes, add cement and water reducer in turn and mix them thoroughly, continue stirring for 10 minutes, add the remaining water, stir evenly to obtain slurry;

[0086] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 6.0kg / m 3 Water reducing agent;

[0087] pouring, spraying curing agent 60min and 150min after pouring, curing, and obtaining concrete;

[0088] The preparation process of the curing agent is the same as that of Comparative Example 2. Comparative Example 6

[0089] Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 8 minutes, add cement and water reducing agent in turn and mix them thoroughly, continue to stir for 10 minutes, add the remaining water, stir evenly to obtain slurry; discharge and cure to obtain concrete;

[0090] The slurry includes the following components: 320kg / m 3 Cement, 55kg / m 3 Fly ash, 745kg / m 3 River sand, 1072kg / m 3 Coarse aggregate, 157kg / m 3 Water, 6.0kg / m 3 Water reducing agent.

[0091] experiment

[0092] The concrete obtained in Examples 1-3 and Comparative Examples 1-6 were taken to prepare samples, and their properties were tested and the test results were recorded:

[0093] Taking GB / T 50081 as the reference standard, the mechanical properties of concrete specimens after curing for 60 days were tested. The size of the compressive strength specimen was 150mm×150mm×150mm, and the size of the elastic modulus specimen was 150mm×150mm×300mm.

[0094] With reference to GB / T 29417, the slurry was poured to a size of 100 mm × 100 mm × 515 mm. The material was discharged and the curing agent was sprayed in the manner of the above-mentioned embodiment and comparative example. After forming, the concrete sample was left to stand at room temperature for 24 hours and then demolded to obtain the concrete sample. The sample was moved to a shrinkage room and the shrinkage rate of the sample after 60 days was detected using a micrometer. The experimental temperature was 20°C and the relative humidity was 60%.

[0095] Taking GB 50082 as the reference standard, the slurry was poured into a flat thin plate mold of 600mm×600mm×100mm, and the material was discharged and the curing agent was sprayed in the manner of the above-mentioned embodiment and comparative example. The mold was removed after curing for 7 days to obtain a concrete sample. A 100x reading microscope was used to observe and measure the maximum width of each crack, and the total crack area per unit area of ​​the sample was detected.

[0096]

[0097] According to the data in the above table, we can clearly draw the following conclusions:

[0098] The concrete obtained in Examples 1-3 is compared with the concrete obtained in Comparative Examples 1-6. The test results show that:

[0099] Compared with comparative examples 1-6, the concrete obtained in Examples 1-3 has better compressive strength and elastic modulus data, and lower shrinkage rate and total crack area values; this fully demonstrates that the present application achieves an improvement in the strength and crack resistance of the prepared concrete.

[0100] Compared with Example 1, the concrete obtained in Comparative Examples 1-3 has different preparation processes and components of the anti-cracking agent; compared with Example 3, the concrete obtained in Comparative Examples 4-6 has different preparation processes and components of the curing agent; the compressive strength, elastic modulus data, shrinkage rate, and total cracking area data of the concrete obtained in Comparative Examples 1-6 are deteriorated; it can be seen that the setting of the preparation process of the anti-cracking agent and the curing agent and the components used in the present application can promote the improvement of the strength and crack resistance of the prepared concrete.

[0101] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.

[0102] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing reinforced anti-cracking concrete for prefabricated buildings, characterized in that: Including the following processes: Take fly ash, river sand, coarse aggregate and half of the water, mix them, stir for 5 to 8 minutes, add cement, anti-cracking agent and water reducing agent in turn and mix them thoroughly, continue to stir for 5 to 10 minutes, add the remaining water, stir evenly to obtain slurry; pour, spray curing agent 60 minutes and 150 minutes after pouring, and cure to obtain concrete; The anti-cracking agent is prepared by the following process: S1. Take dichloromethane, add phenylboric acid and diallylpentylamine, mix, introduce oxygen, add organic boron, pyridine and cuprous oxide, and heat at 80-85°C. Under 4.0MPa, the reaction was carried out for 24h to obtain a monomer; S2. Take deionized water, add monomer and acrylamide to mix to obtain an acrylamide solution; Adding acrylic acid aqueous solution and ammonium persulfate aqueous solution, reacting at 50-60° C. for 40-60 minutes to obtain polyacrylamide aqueous solution; drying and crushing to obtain polyacrylamide particles; The polyacrylamide aqueous solution is prepared into a 0.5-2.0% finishing solution, the polypropylene fiber is immersed in the solution, and the solution is soaked at a temperature of 45-55°C for 24 hours, and then the fiber is taken out and air-dried to obtain the treated fiber; Mixing with polyacrylamide particles to obtain an anti-cracking agent; The organic boron is boron trifluoride ether solution; The curing agent is prepared by the following process: Take polyacrylamide particles and mix with water, add sodium hydroxide, heat to 95°C for hydrolysis for 2 hours; add montmorillonite and surfactant, mix to obtain a curing agent.

2. The method for preparing the reinforced anti-cracking concrete for prefabricated buildings according to claim 1, characterized in that: The slurry includes the following components by mass: 320 parts of cement, 55 parts of fly ash, 745 parts of river sand, 1072 parts of coarse aggregate, 157 parts of water, 3.8-6.0 parts of water reducing agent, and 20.6-30.5 parts of anti-cracking agent.

3. The method for preparing the reinforced anti-cracking concrete for prefabricated buildings according to claim 1, characterized in that: The molar ratio of the phenylboric acid, diallylamine, organic boron, pyridine and cuprous oxide is 1:(1.0-1.1):(0.08-0.11):(0.20-0.22):

3.

4. The method for preparing the reinforced anti-cracking concrete for prefabricated buildings according to claim 1, characterized in that: The mass ratio of deionized water, monomer and acrylamide in the acrylamide solution is (20-50):(0.3-0.5):

1.

5. The method for preparing the reinforced anti-cracking concrete for prefabricated buildings according to claim 1, characterized in that: The volume ratio of the acrylamide solution, the acrylic acid aqueous solution and the ammonium persulfate aqueous solution is 100:50:0.

5.

6. The method for preparing the reinforced anti-cracking concrete for prefabricated buildings according to claim 1, characterized in that: The mass ratio of the polypropylene fiber to the finishing liquid is 1:(10-20).

7. The method for preparing the reinforced anti-cracking concrete for prefabricated buildings according to claim 1, characterized in that: The mass ratio of polyacrylamide particles to treated fibers in the anti-cracking agent is 1:(1-3).

8. A reinforced anti-cracking concrete for prefabricated buildings prepared according to the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Anti-crack concrete and preparation method thereof

    CN111377675A